Formação em serviço sobre gestão de escolas inclusivas para diretores de escolas de educação infantil - Carneiro, Relma Urel Carbone (Universidade Federal de São Carlos, 2006)
We live in the context of a global society, in which changes are demanded in all aspects in the search for a better quality of life for mankind. In addition, there is an increase in the proportion of excluded individuals and thus there has been much discussion on social inclusion in political and educational debates. The school, as a segment of society, has also been facing the task to offer a better quality of education to all children. In the specific case of children with special needs, there has also been discussion within the concept of inclusive schools, which should be open to the differences. Considering the current demands, improvements in the qualifications of school teams is fundamental to assure the necessary transformation of schools, and the national research on school inclusion has been contributing to the problem of formation and work of teachers. However, it should be remembered that the leader role played by the school director has been identified as a primary factor for the achievement of increasingly inclusive schools. Thus, considering that this role played by the director requires new knowledge, attitudes and abilities to deal with the current conditions and emerging tendencies in general and special education, the present study aimed to develop, establish and evaluate a training program for directors of child schools, from the standpoint of school inclusion. Initially, a study was conducted on the professional profile of the school directors and their needs, by observation of the work routine of a director for four months, comprising 21 visits for observation and analysis of school records (school planning and statute). Thereafter, several people were interviewed (the director, the teacher of a student with special needs, the parents of this student, and the pedagogue assisting this child at a specialized center) with a view to achieve more knowledge on the role played by the director from the standpoint of each of these individuals. Based on the collected data and concepts developed by authors in the field of school management and inclusion, a closed questionnaire was prepared and sent to all 60 directors of municipal child schools from the city of Bauru, to collect further information on the training needs of these professionals to allow them to work as managers of inclusive schools. The results of this first study indicated that, even though they have legal knowledge on the policies of school inclusion, in practice the role played by the director seemed to be characterized by emphasis on bureaucratic issues of the school, centralization of decisions and lack of knowledge on how to respond to the educational demands of individuals with special needs. Following, a training program was developed and established for 41 directors of child schools. The program comprised theoretical issues on the problem of inclusion and practical activities of management and solution of problems related to the actual difficulties of daily work. The program was evaluated by: a) tests for group resolution of the same problem situations, at onset and completion of the program, b) personal reports on people with special needs collected before the program, c) reports based on a questionnaire with five open questions on the changes observed after the course perceived by the directors themselves, and d) a closed questionnaire on the formal aspects of the program. The results indicated that the program yielded the expected results in the perceptions and attitudes of directors, at least from their reports. Discussion was based on the conclusion that, even though such initiatives of training programs are necessary, they are not sufficient, since the transfer of changes from reports to the educational practices in the daily life of schools is not automatic, which suggests that training should go further and assure follow-up by collective work and establishment of a culture of collaboration and appreciation of human diversity. Finally, the way to change seems to be focused on the challenging role of the director, who must have a firm leadership yet simultaneously must promote collective processes of planning, organization and development of the political-pedagogical project of the school
Keywords: Educação especial; Inclusão Escolar; Gestão escolar; Formação continuada; Special education; School inclusion; School management; Continued education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL